The effect of pregnancy yoga exercise on reducing anxiety of pregnant woman third trimester - Rahayu, Kusila Devia; Dela Rosa, Ronnell D.; Handayani, Wardah (The Journal of Palembang Nursing Studies, 2023)
Background: Physiological changes and fear of facing labor in the third trimester of pregnancy can trigger increased anxiety in pregnant women. One of the interventions to reduce anxiety in third trimester pregnant women is yoga exercise. Objective: The purpose of this study was to determine the effect of pregnant yoga exercise on reducing anxiety pregnant women in the third trimester. Methods: This quantitative research uses a pure experimental research design with pre and post-test control group techniques. The number of respondents was 30 and divided into the intervention group and the control group. Data collection using The Pranaya Pregnancy Yoga Exercise Protocol and PASS questionnaire. The pregnancy yoga exercise protocol was used after passing the feasibility test using The Dolphin Yoga Assessment Tool and PASS questionnaire used after passing the validity and reliability test. Bivariate data analysis was performed using the Man-Whitney non-parametric test. The test was carried out after the data passed the normality test using the Shapiro-Wilks test. Results: This study showed that yoga interventions during pregnancy had a significant effect on reducing anxiety in third trimester pregnant women with a p < 0.001. Conclusions: Health workers need to make innovative interventions that can improve the mental health of pregnant women, for example through the activation of the pregnant women class program.